The Impact of Macroeconomic on Working Capital Management. Empirical Study in Indonesian firms Before Pandemic 19. - Ira; Heru Kristanto (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2022)
Working capital management is determined by investment policies, funding policies and, stability in macroeconomic conditions. This study aims to examine the effect of cash, receivables, inventory and working capital on firm value. Test the moderation of macroeconomic variables on the effect of working capital on firm value. This study uses a purposive sampling method for companies listed on the IDX, with a study period of 2009-2018. Total observations or n samples are 1960. Hypothesis testing uses the panel of fixed-effect regression and moderation regression. The results of research or hypothesis testing indicate that cash, receivables and inventories have a positive effect on firm value. Working capital has a positive effect on firm value. Inflation, rupiah exchange rates and risk-free interest rates moderate the effect of working capital on the firm's value. The implication of this research is that good working capital management will increase company value. Macroeconomic conditions of a country will affect the management of working capital and company value.